2018
DOI: 10.22334/jbhost.v4i2.125
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Destination Images on Revisit Intention in Mount Batur

Abstract: Tourism has become one of idol business in Indonesia, which can be seen by the graph of performance continues to rise up compared to oil, gas, coal, and palm oil which continue to decline. Each destination tries to serve tourists better using many kinds of strategies, one of them is the destination image. This research aims to analyze the influence of destination image on the revisit intention in Mount Batur, Bali. The study is explanatory and done using quantitative and descriptive approaches. The num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
(2 reference statements)
1
3
0
Order By: Relevance
“…This study found that: Travel Experience (X1) significantly and positively affects revisit intention (Y) on Monkey Forest Ubud. This is in line with previous research entitled The Influence of Customer Experience to Revisit Intention in Pandawa Beach Attraction, the results of this study indicate a positive influence between travel experience and revisit intention (Agustina, 2018;Hung et al, 2016). This means Monkey Forest Ubud can create a travel experience for tourists who have visited so that these tourists do revisit intention.…”
Section: Discussionsupporting
confidence: 92%
“…This study found that: Travel Experience (X1) significantly and positively affects revisit intention (Y) on Monkey Forest Ubud. This is in line with previous research entitled The Influence of Customer Experience to Revisit Intention in Pandawa Beach Attraction, the results of this study indicate a positive influence between travel experience and revisit intention (Agustina, 2018;Hung et al, 2016). This means Monkey Forest Ubud can create a travel experience for tourists who have visited so that these tourists do revisit intention.…”
Section: Discussionsupporting
confidence: 92%
“…Analogically, it is recognized that positive DIs are more likely to achieve high satisfaction levels and, conversely, negative images achieve high dissatisfaction levels, which means that satisfied visitors will come back to a favorable destination (Shafiee et al, 2016;King et al, 2015). Therefore, boosting an attractive DI is necessary to enhance intentions to revisit a place (Agustina, 2018). Based on these discussions, the next hypotheses formulated are as follows:…”
Section: Destination Imagementioning
confidence: 99%
“…The majority of the study's findings indicated that satisfaction appears to be fulfilled by an image of a destination. It acts as a motivator for tourists to return (Barkah and Febriasari, 2021), because people are motivated to return to a place that they find appealing (Agustina, 2018). It supports the idea that when there is a positive image of a destination, people are more likely to visit it.…”
Section: Tourist's Revisit Intentionmentioning
confidence: 91%